A highly enantioselective Biginelli reaction using self-assembled methanoproline–thiourea organocatalysts: asymmetric synthesis of 6-isopropyl-3, 4-dihydropyrimidines. Issue 1 (26th October 2015) - Hang, Zhijun; Zhu, Jun; Lian, Xiang; Xu, Peng; Yu, Han; Han, Sheng
Abstract : An efficient self-assembled methanoproline–thiourea organocatalyst for the synthesis of optically active 6-isopropyl-3, 4-dihydropyrimidines via an asymmetric Biginelli reaction was developed, which is superior to the individual precatalyst. Abstract : An efficient self-assembled methanoproline–thiourea organocatalyst for the synthesis of optically active 6-isopropyl-3, 4-dihydro-pyrimidines via an asymmetric Biginelli reaction was developed, which is superior to the individual precatalyst. A wide range of optically active 6-isopropyl-3, 4-dihydropyrimidines with remarkable pharmacological interest was obtained in high yields with excellent enantioselectivities (up to 99% ee). A plausible transition state has been proposed to explain the origin of the activation and the asymmetric induction.